A dish with no fish: How DHA-free microalgae and linseed oil enhance n-3 LC-PUFA biosynthesis in rainbow trout (Oncorhynchus mykiss) - Anna Simon; Sebastian Lippemeier; Flora Suess; Jonas Mueller; Alexander Rebl; Michael Schlachter; Frederik Kaiser; Carsten Schulz (Aquaculture, 2026)

Soil organic carbon sequestration over 50 years in resampled afforestation chronosequences on former cropland - Ming Yu; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Teresa G. Bárcena; Inger Kappel Schmidt; Per Gundersen; Ludovica D'Imperio; Carsten W. Mueller; Lars Vesterdal (Journal of Environmental Management, 2026)

A fatty fate: How different dietary microalgae affect the fatty acid metabolism and deposition in rainbow trout (Oncorhynchus mykiss) - Anna Simon; Sebastian Lippemeier; Jonas Nowaczek; Jonas Mueller; Alexander Rebl; Frederik Kaiser; Carsten Schulz (Aquaculture, 2026)

Soil drying shapes rhizosheath properties and their link with maize yields across different soils - Franziska A. Steiner; Shu-Yin Tung; Andreas J. Wild; Tina Köhler; Nicolas Tyborski; Andrea Carminati; Johanna Pausch; Tillmann Lüders; Sebastian Wolfrum; Carsten W. Mueller; Alix Vidal (Plant and Soil, 2025)
Background and Aims Biophysicochemical soil properties in the rhizosheath are pivotal for crop yields and drive organic carbon cycling in agricultural soils. Yet, it remains uncertain how moderate soil drought may alter and interfere with rhizosheath properties in diverse soil types, and whether specific rhizosheath traits benefit crop yields under different water availability in heterogeneous field environments. Methods Maize ( Zea mays L.) was grown under ambient precipitation and moderate drought (60% precipitation exclusion) at two field sites differing in physicochemical soil properties, such as texture and amounts of soil organic matter (SOM). Rhizosheath properties, namely soil aggregation as well as content and distribution of carbon (C) and nitrogen (N), were analyzed and, in conjunction with root traits, related to maize yields. Results Under moderate soil drought, net rhizosheath-C concentrated spatially within the smaller rhizosheath in the form of more carbon-rich rhizodeposits. These effects were mediated by native soil properties, with rhizosheath structural stability decreasing stronger under drought in the finer-textured soil, allocating greater proportions of C and N to microaggregates. Rhizosheath and root properties were associated with maize yields. Yet, the influence and importance of belowground traits for crop yields varied with environmental conditions (soil x precipitation). Conclusion The responsiveness of rhizosheath properties to moderate soil drought may influence the fate and turnover of root-derived C, and thus the overall drought resilience of SOM in agricultural soils. Moreover, our findings underscore the importance of rhizosheath properties for crop yields, yet highlighting that these relationships differ among environmental scenarios.

A question of digestion: How microalgae species affects lipid and fatty acid digestibility in rainbow trout (Oncorhynchus mykiss) - Anna Simon; Sebastian Lippemeier; Jonas Mueller; Michael Schlachter; Frederik Kaiser; Carsten Schulz (Aquaculture, 2024)

Transcriptomic Point of Departure (tPOD) of androstenedione in zebrafish embryos as a potential surrogate for chronic endpoints - Fabian Essfeld; Steve U. Ayobahan; Jannis Strompen; Julia Alvincz; Heike Schmidt-Posthaus; Jan Woelz; Till Mueller; Benedikt Ringbeck; Matthias Teigeler; Elke Eilebrecht; Sebastian Eilebrecht (Science of The Total Environment, 2024)

Terminal glacial overdeepenings: Patterns of erosion, infilling and new constraints on the glaciation history of Northern Switzerland - Marius W. Buechi; Angela Landgraf; Herfried Madritsch; Daniela Mueller; Maria Knipping; Franziska Nyffenegger; Frank Preusser; Sebastian Schaller; Michael Schnellmann; Gaudenz Deplazes (Quaternary Science Reviews, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Decentralised system for demand-oriented collection of food waste – Assessment of biomethane potential, pathogen development and microbial community structure - Marco Wehner; Irene Kleidorfer; Ingrid Whittle; Daniela Bischof; Anke Bockreis; Heribert Insam; Wolfgang Mueller; Sebastian Hupfauf (Bioresource Technology, 2023)

Neuronavigated repetitive transcranial magnetic stimulation as novel mapping technique provides insights into language function in primary progressive aphasia - Felix Mueller-Sarnowski; Nico Sollmann; Axel Schröder; Leen Houri; Sebastian Ille; Timo Grimmer; Sandro M. Krieg; Janine Diehl-Schmid (Brain Imaging and Behavior, 2022)
Navigated repetitive transcranial magnetic stimulation (nrTMS) is an innovative technique that provides insight into language function with high accuracy in time and space. So far, nrTMS has mainly been applied in presurgical language mapping of patients with intracranial neoplasms. For the present study, nrTMS was used for language mapping in primary progressive aphasia (PPA). Seven patients (median age: 70 years, 4 males) with the non-fluent variant of PPA (nfvPPA) were included in this pilot study. Trains of nrTMS (5 Hz, 100% resting motor threshold) caused virtual lesions at 46 standardized cortical stimulation targets per hemisphere. Patients’ errors in a naming task during stimulation were counted. The majority of errors induced occurred during frontal lobe stimulation (34.3%). Timing errors and non-responses were most frequent. More errors were induced in the right hemisphere (58%) than in the left hemisphere (42%). Mapping was tolerated by all patients, however, discomfort or pain was reported for stimulation of frontal areas. The elevated right-hemispheric error rate in our study could be due to a partial shift of language function to the right hemisphere in neurodegenerative aphasia during the course of disease and therefore points to the existence of neuronal plasticity in nfvPPA. While this is an interesting finding for neurodegenerative disorders per se, its promotion might also harbor future therapeutic targets.

The lifecycle of volcanic ash: advances and ongoing challenges - Joali Paredes-Mariño; Pablo Forte; Stefano Alois; Ka Lok Chan; Valeria Cigala; Sebastian B. Mueller; Matthieu Poret; Antonio Spanu; Ines Tomašek; Pierre-Yves Tournigand; Diego Perugini; Ulrich Kueppers (Bulletin of Volcanology, 2022)
Explosive volcanic eruptions can produce vast amounts of volcanic ash made up mainly of fragments of magmatic glass, country rock and minerals < 2 mm in size. Ash particles forming from magma fragmentation are generated by several processes when brittle response accommodates (local) deformation stress that exceeds the capability of the bulk material to respond by viscous flow. These processes span a wide range of temperatures, can occur inside or outside the volcanic edifice and can involve all melt compositions. Ash is then dispersed by volcanic and atmospheric processes over large distances and can have global distributions. Explosive eruptions have repeatedly drawn focus to studying volcanic ash. The continued occurrence of such eruptions worldwide and their widespread impacts motivates the study of the chemical and physical processes involved in the lifecycle of volcanic ash (e.g. magma fragmentation, particle aggregation), as well as the immediate to long-term effects (e.g. water and air pollution, soil fertilization) and consequences (e.g. environmental, economic, social) associated with ashfall. In this perspectives article, we reflect on the progress made over the last two decades in understanding (1) volcanic ash generation; (2) dispersion, sedimentation and erosion; and (3) impacts on the atmosphere, hydrosphere, biosphere and modern infrastructure. Finally, we discuss open questions and future challenges.

Journal Club - Fabian M. Commichau; Jannis Anstatt; Sven Krappmann; Evi Stegmann; Sebastian Banhart; Kai Papenfort; Sascha Brunke; Bernhard Hube; Marc Bramkamp; Miriam Herbert; Johannes Sander; Jonathan Wolf Mueller; et al. (BIOspektrum, 2020)

Journal Club - Sandra Wiegand; Daniela Kruck; Sebastian Lücker; Johannes Sander; Jonathan Wolf Mueller (BIOspektrum, 2019)

Total grain size distribution of an intense Hawaiian fountaining event: case study of the 1959 Kīlauea Iki eruption - Sebastian B Mueller; Bruce F Houghton; Donald A Swanson; Matthieu Poret; Sarah A Fagents (Bulletin of Volcanology, 2019)

Diversity of soluble salt concentrations on volcanic ash aggregates from a variety of eruption types and deposits - Mathieu Colombier; Sebastian B. Mueller; Ulrich Kueppers; Bettina Scheu; Pierre Delmelle; Corrado Cimarelli; Shane J. Cronin; Richard J. Brown; Manuela Tost; Donald B. Dingwell (Bulletin of Volcanology, 2019)

Intricate episodic growth of a Hawaiian tephra deposit: case study of the 1959 Kīlauea Iki eruption - Sebastian B. Mueller; Bruce F. Houghton; Donald A. Swanson; Sarah A. Fagents; Malin Klawonn (Bulletin of Volcanology, 2018)

Aggregation in particle rich environments: a textural study of examples from volcanic eruptions, meteorite impacts, and fluidized bed processing - Sebastian B. Mueller; Ulrich Kueppers; Matthew S. Huber; Kai-Uwe Hess; Gisela Poesges; Bernhard Ruthensteiner; Donald B. Dingwell (Bulletin of Volcanology, 2018)

High Pneumocystis jirovecii colonization rate among haemodialysis patients - Carlos Fritzsche; Hosam Ghanem; Sebastian Koball; Brigitte Mueller-Hilke; Emil C. Reisinger (Infectious Diseases, 2017)

Large amounts of labile organic carbon in permafrost soils of northern A laska - Carsten W. Mueller; Janet Rethemeyer; Jenny Kao‐Kniffin; Sebastian Löppmann; Kenneth M. Hinkel; James G. Bockheim (Global Change Biology, 2015)
Permafrost‐affected soils of the northern circumpolar region represent 50% of the terrestrial soil organic carbon ( SOC ) reservoir and are most strongly affected by climatic change. There is growing concern that this vast SOC pool could transition from a net C sink to a source. But so far little is known on how the organic matter ( OM ) in permafrost soils will respond in a warming future, which is governed by OM composition and possible stabilization mechanisms. To investigate if and how SOC in the active layer and adjacent permafrost is protected against degradation, we employed density fractionation to separate differently stabilized SOM fractions. We studied the quantity and quality of OM in different compartments using elemental analysis, 13 C solid‐phase nuclear magnetic resonance ( 13 C ‐ NMR ) spectroscopy, and 14 C analyses. The soil samples were derived from 16 cores from drained thaw lake basins, ranging from 0 to 5500 years of age, representing a unique series of developing Arctic soils over time. The normalized SOC stocks ranged between 35.5 and 86.2 kg SOC m −3 , with the major amount of SOC located in the active layers. The SOC stock is dominated by large amounts of particulate organic matter ( POM ), whereas mineral‐associated OM especially in older soils is of minor importance on a mass basis. We show that tremendous amounts of over 25 kg OC per square meter are stored as presumably easily degradable OM rich in carbohydrates. Only about 10 kg OC per square meter is present as presumably more stable, mineral‐associated OC . Significant amounts of the easily degradable, carbohydrate‐rich OM are preserved in the yet permanently frozen soil below the permafrost table. Forced by global warming, this vast labile OM pool could soon become available for microbial degradation due to the continuous deepening of the annually thawing active layer.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

High-load resistance exercise with superimposed vibration and vascular occlusion increases critical power, capillaries and lean mass in endurance-trained men - Sandro Manuel Mueller; David Aguayo; Fabio Lunardi; Severin Ruoss; Urs Boutellier; Sebastian Frese; Jens A. Petersen; Hans H. Jung; Marco Toigo (European Journal of Applied Physiology, 2014)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Siderophore-mediated iron trafficking in humans is regulated by iron - Zhuoming Liu; Robert Lanford; Sebastian Mueller; Glenn S. Gerhard; Sara Luscieti; Mayka Sanchez; L. Devireddy (Journal of Molecular Medicine, 2012)

Simultaneous isolation of pure and intact chloroplasts and mitochondria from moss as the basis for sub-cellular proteomics - Erika G. E. Lang; Stefanie J. Mueller; Sebastian N. W. Hoernstein; Joanna Porankiewicz-Asplund; Marco Vervliet-Scheebaum; Ralf Reski (Plant Cell Reports, 2011)

Angiotensin II triggers release of leukotriene C4 in vascular smooth muscle cells via the multidrug resistance-related protein 1 - Cornelius F. H. Mueller; Marc Ulrich Becher; Sebastian Zimmer; Sven Wassmann; Barbara Keuler; Georg Nickenig (Molecular and Cellular Biochemistry, 2010)

Interaction of Inhibitor of DNA binding 3 (Id3) with Gut-enriched Krüppel-like factor (GKLF) and p53 regulates proliferation of vascular smooth muscle cells - Kerstin Wassmann; Cornelius F. H. Mueller; Ulrich M. Becher; Christian Werner; Alexander Jung; Sebastian Zimmer; Martin Steinmetz; Georg Nickenig; Sven Wassmann (Molecular and Cellular Biochemistry, 2010)

Initial differentiation of vertical soil organic matter distribution and composition under juvenile beech (Fagus sylvatica L.) trees - Carsten W. Mueller; Nicolas Brüggemann; Karin Pritsch; Gunda Stoelken; Sebastian Gayler; J. Barbro Winkler; Ingrid Kögel-Knabner (Plant and Soil, 2009)

No clinically relevant CYP3A induction after St. John’s wort with low hyperforin content in healthy volunteers - Silke C. Mueller; Jolanta Majcher-Peszynska; Ralf G. Mundkowski; Bernhard Uehleke; Sebastian Klammt; Hartwig Sievers; Romanus Lehnfeld; Bruno Frank; Kerstin Thurow; Guenther Kundt; Bernd Drewelow (European Journal of Clinical Pharmacology, 2009)

The extent of induction of CYP3A by St. John’s wort varies among products and is linked to hyperforin dose - Silke C. Mueller; Jolanta Majcher-Peszynska; Bernhard Uehleke; Sebastian Klammt; Ralf G. Mundkowski; Wolfram Miekisch; Hartwig Sievers; Steffen Bauer; Bruno Frank; Guenther Kundt; Bernd Drewelow (European Journal of Clinical Pharmacology, 2006)

Permeability and degassing of dome lavas undergoing rapid decompression: An experimental determination - Sebastian Mueller; Oleg Melnik; Oliver Spieler; Bettina Scheu; Donald B. Dingwell (Bulletin of Volcanology, 2005)